Sanctity of contract under Islamic law: an expository study with special reference to the Malaysian Islamic banking cases - Othman, Ahmad Azam (Serials Publications, 2014)
This article is on the concept of sanctity of contract under Islamic law with special reference to decided cases on Islamic banking in Malaysia. Islamic law recognizes generally the concept of sanctity of contract that is based on the principle that every contract needs to be fulfilled and every contracting party is obliged to honour to what has been agreed upon accordingly. Muslim jurists have discussed such concept in detail in their writings. The concept involves the principles of freedom of the contracting parties to agree and stipulate any condition they like. Thus, the examination and analysis on the Muslim jurists discourse on these principles are carried out. This paper aims to achieve the following objectives: To analyse the concept of sanctity of contract together with the freedom of the contracting parties to agree and stipulate under Islamic law in detail and to analyse the principles of sanctity of contract that have been applied in various Islamic cases in Malaysian. The main methodology to be adopted for this research is a library research. Thus, relevant published materials available in the library in the form of books, articles, research papers, reported cases and the likes either in English, Arabic or Malay are consulted. The reference to the publications in the websites and Internet sources are also referred to. In short, it is hoped that the paper has shown that Islamic law recognizes the concept of sanctity of contract and it is a welldefined one.